Analysis Of Results Of Voltage Transformer Insulation Resistance Test On Bay Banda Aceh 1 And Bay Banda Aceh 2 Conductors At Ulee Kareng Substation - Hari Andiko; Muhammad Erpandi Dalimunthe (Sean Institute, 2025)
Voltage transformers are one of the important components in an electric power system that functions to reduce the voltage from the transmission network to a lower level for measurement and protection purposes. The quality of the insulation of the voltage transformer greatly affects the reliability of the operation of the electric power system. Therefore, periodic insulation resistance testing is needed to ensure optimal insulation performance and avoid electrical interference. This study aims to analyze the results of the insulation resistance test on the voltage transformer used in the Bay Banda Aceh 1 and Bay Banda Aceh 2 conductors at the Ulee Kareng Substation. The test was carried out using a megger test tool with a method of measuring the insulation resistance between the primary winding and the ground and between the primary winding and the secondary. The measurement data were compared with applicable standards to determine the insulation condition of the voltage transformer. The results of the study showed that the insulation resistance values ​​obtained from both conductors had variations that were influenced by environmental factors such as temperature and humidity. Based on the analysis carried out, most of the test results were still within safe limits according to IEEE and SPLN standards. However, there were several test values ​​that were close to the minimum limit, which indicated insulation degradation that needed further attention. With this research, it is expected to provide information on the condition of voltage transformer insulation and recommendations for preventive actions needed to maintain the reliability of the electric power system at the Ulee Kareng Substation.